Intervention of childhood and adolescents obesity in Shantou city. Issue 4 (July 2015) - Guo, Haiting; Zeng, Xiaoshan; Zhuang, Qiaoyu; Zheng, Yubin; Chen, Shenren
Summary: Objectives: The purpose of this study was to evaluate the effects of multicomponent school based intervention constituted of diet modification, regular exercise and psychosocial consultation on body status in overweight and obese children and adolescents. And to come up with an appropriate intervention protocol for controlling children and adolescents obesity in Shantou city. Methods: Two schools were randomised to intervention group and control group respectively. A total of 41 students enrolled were diagnosed as overweight or obese. Twenty-six students of the intervention group completed the one-year intervention programme consisted of diet modification, regular exercise and psychological consultation except two of them were transferred to another school. The differences of BMI, anthropometric measures, metabolic profile and the scores of questionnaire and the scale were compared to evaluate the effects of the intervention programme. Results: After one-year intervention, it observed in the intervention group that BMI-Z score, WHR and WHtR had significant improvements, and there was a nonsignificant trend ( P  = 0.053) for a decrease in BMI-P. Fasting plasma glucose, cholesterol (CH) and low-density-lipoprotein cholesterol (LDL-C) levels in the intervention group showed nonsignificant trend for a decrease (PFPG = 0.084, PCH = 0.057, PLDLC = 0.098), compared with a significant increase of triglycerides (TG) and LDL-C levels in the control group (PTG = 0.041, PLDL-C = 0.038). There were some positive dietary, physical activity, or sedentary behaviour changes found in the students of the intervention group as the scores of the questionnaire got significant improvement ( P  = 0.04). Conclusions: Our one-year multicomponent school-based intervention programme did have positive effects to some extents on health state and lifestyle behaviour of overweight and obese children and adolescents, which indicated that it is feasible and important to implement such a school-based intervention programme in Shantou city.